Academic advocacy in public health: Disciplinary 'duty' or political 'propaganda'?. (September 2017) - Smith, K.E.; Stewart, E.A.
Abstract: The role of 'advocacy' within public health attracts considerable debate but is rarely the subject of empirical research. This paper reviews the available literature and presents data from qualitative research (interviews and focus groups conducted in the UK in 2011–2013) involving 147 professionals (working in academia, the public sector, the third sector and policy settings) concerned with public health in the UK. It seeks to address the following questions: (i) What is public health advocacy and how does it relate to research?; (ii) What role (if any) do professionals concerned with public health feel researchers ought to play in advocacy?; and (iii) For those researchers who do engage in advocacy, what are the risks and challenges and to what extent can these be managed/mitigated? In answering these questions, we argue that two deeply contrasting conceptualisations of 'advocacy' exist within public health, the most dominant of which ('representational') centres on strategies for 'selling' public health goals to decision-makers and the wider public. This contrasts with an alternative (less widely employed) conceptualisation of advocacy as 'facilitational'. This approach focuses on working with communities whose voices are often unheard/ignored in policy to enable their views to contribute to debates. We argue that these divergent ways of thinking about advocacy speak to a more fundamental challenge regarding the role of the public in research, policy and practice and the activities that connect these various strands of public health research. Highlights: Explores implications of calls for researchers to engage in public health advocacy. Outlines two deeply contrasting, popular definitions of public health advocacy. Highlights major risks of researcher involvement in public health advocacy. Discusses ways in which such risks might be managed, including via training. Argues public health advocacy needs more dialogic and democratic approaches.